2020
DOI: 10.7759/cureus.10544
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Atherogenic Inflammatory Mediators in Inflammatory Bowel Disease Patients Increase the Risk of Thrombosis, Coronary Artery Disease, and Myocardial Infarction: A Scientific Dilemma

Abstract: Inflammatory bowel disease (IBD), comprising ulcerative colitis and Crohn's disease, is characterized by widespread inflammation of the gastrointestinal tract with systemic manifestations. Inflammation is one of the driving forces for the pathogenesis of atherosclerosis and its dreaded complications like myocardial infarction (MI). Yet, the association between IBD and myocardial infarction has not been thoroughly established. Myocardial infarction in IBD patients was predominantly seen in young women during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
1
0
4
Order By: Relevance
“…Эндотелиальная дисфункция ускоряет процесс образования атеросклеротической бляшки и ремоделирования стенки сосуда. Хроническое системное воспаление опасно и тем, что при росте бляшки у нее образуется тонкая покрышка, что создает опасность её разрыва и развития таких осложнений как инфаркт миокарда или инсульт головного мозга [2]. Существует целый ряд данных, подтверждающих теоретические предположения.…”
Section: Discussionunclassified
“…Эндотелиальная дисфункция ускоряет процесс образования атеросклеротической бляшки и ремоделирования стенки сосуда. Хроническое системное воспаление опасно и тем, что при росте бляшки у нее образуется тонкая покрышка, что создает опасность её разрыва и развития таких осложнений как инфаркт миокарда или инсульт головного мозга [2]. Существует целый ряд данных, подтверждающих теоретические предположения.…”
Section: Discussionunclassified
“…показано, что венозная тромбоэмболия значительно выше у пациентов с ВЗК (6,2%) по сравнению с контрольной группой (1,6%) или пациентами с ревматоидным артритом (2,1%), а 77% тромботических событий произошло, когда пациенты с ВЗК находились в клинической ремиссии [10]. Тромбоз глубоких вен и тромбоэмболия легочной артерии -распространенные осложнения, возникающие в состоянии гиперкоагуляции при ВЗК [1]. В условиях воспалительного процесса цитокины ИЛ-1, 6, ФНО-α, ИЛ-8, интерферон-α индуцируют высвобождение тканевого фактора (фактора свертывания крови III) моноцитами.…”
Section: патофизиология взаимосвязи взк и атеросклерозаunclassified
“…Примерно 29% всех пациентов с ВЗК являются активными курильщиками [24]. Имеются противоречивые дан- [1,25]. Однако, учитывая, что курение является важнейшим фактором развития атеросклероза и ишемической болезни сердца (ИБС), всем пациентам с ВЗК целесообразно рекомендовать полный отказ от курения.…”
Section: общие фр взк и атеросклерозаunclassified
See 1 more Smart Citation
“…For example, one study showed that IL-12α suppresses lymphocyte proliferation and ameliorates autoimmune uveitis in mice by antagonizing pathogenic Th17 responses through induction of IL-10 and IL-35-expressing regulatory B cells ( 27 ), while other studies demonstrated that inhibition of IL-12α by genetic deletion significantly attenuated macrophage polarization, T cell derived interferon-γ (IFN-γ) production, and cardiac injury repair after myocardial infarction ( 28 ). Importantly, clinical trials have demonstrated that co-inhibition of IL-12/IL-23 signaling was effective in treating ulcerative colitis or Crohn’s disease ( 29 31 ), while inhibition of IL-23 signaling alone was not effective in treating ulcerative colitis or Crohn’s disease ( 32 , 33 ), indicating that IL-12 signaling is essential for the development of ulcerative colitis, a disease showed a significantly high risk of heart attack and HF development ( 34 , 35 ). However, the role of IL-12α in chronic pressure overload-induced cardiopulmonary inflammation, HF development and HF progression has not been previously studied.…”
Section: Introductionmentioning
confidence: 99%